IN VITRO EFFECTS OF A COMMERCIAL HERBAL MEDICINE USED AS AFRICAN TRADITIONAL MEDICINE ON HUMAN NEUTROPHILS - Mothibe, Mmamosheledi Elsie; Kahler-Venter, Christinah; Osuch, Elzbieta (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Commercial herbal medicines (CHMs) being marketed as immune boosters or tonics, have gained widespread popularity. The many herbal mixtures sold have not been tested for efficacy and safety, despite their modern packaging and presentations. It is imperative that these herbal mixtures be investigated for their effects on human neutrophils. Methods: The selected herbal mixture (HM), Stametta™ Body healing liquid, is common in retail outlets in Pretoria, South Africa (SA) and is used as an immune booster or intended to strengthen the body. Isolated neutrophils as well as those in whole blood phagocytes were obtained from blood samples collected from consenting healthy adult volunteers. The neutrophils were incubated with the HM at different strengths, and taken through a luminol-enhanced luminescence assay, using activators- phorbol myristate acetate and N-formyl-methionyl-leucyl-phenylalanine. Results: The HM had variable stimulatory and inhibitory effects on the luminescence activity of healthy isolated and non-isolated human neutrophils. The effects, ranging from weak to potent were either directly or inversely related to the concentration of the HM and were mediated through a direct protein kinase C activating mechanism and an indirect formyl peptide receptor-linked mechanism. Conclusion: The findings have shown the immunomodulatory potential of Stametta TM. The in vitro inhibitory and stimulatory effects on neutrophils which are furthermore time-based, suggest variable effects on the immune system, which may be beneficial as well as risky. The effects at different concentrations highlight the importance of appropriate dosing. It would therefore be prudent to caution users of this commercial herbal medicine accordingly.